2023
DOI: 10.3389/fpain.2023.1217034
|View full text |Cite
|
Sign up to set email alerts
|

Post-anesthetic CPS and EQUUS-FAP scores in surgical and non-surgical equine patients: an observational study

Rachel Anne Reed,
Anna M. Krikorian,
Rose M. Reynolds
et al.

Abstract: BackgroundEquine pain scoring may be affected by the residual effect of anesthetic drugs.ObjectivesTo compare pain scores in the hours immediately following anesthetic recovery to baseline pre-anesthetic scores in equine patients undergoing surgical and non-surgical procedures.Study designClinical observational study.MethodsFifty adult horses undergoing anesthesia for surgical or non-surgical procedures were enrolled. Horses underwent pain scoring using the Composite Pain Score (CPS) and Equine Utrecht Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, since pain is a subjective experience, this approach may not eliminate bias. Additionally, the type and duration of pain need to be researched further, as there are postulations about differences in facial expressions of pain between acute nociceptive and chronic pain and on the effects of general anesthesia ( 14 , 47 , 95 ). These hypotheses, for example, could be tested to improve the understanding and detection of pain in animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since pain is a subjective experience, this approach may not eliminate bias. Additionally, the type and duration of pain need to be researched further, as there are postulations about differences in facial expressions of pain between acute nociceptive and chronic pain and on the effects of general anesthesia ( 14 , 47 , 95 ). These hypotheses, for example, could be tested to improve the understanding and detection of pain in animals.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, animals were assessed both before and after procedures requiring general anesthesia ( 8 , 22 , 27 , 29 , 31 ). However, studies have shown that the facial expression of pain can remain altered for several hours after inhalant anesthesia in both experimental mice and rats ( 45 , 46 ) and in horses ( 47 ). This effect likely holds for other animal species.…”
Section: Facial Expression-based (Grimace) Scales For Animal Pain Ass...mentioning
confidence: 99%